Alexander Vovin. [2005 y 2009] 2020. A Descriptive and Comparative Grammar of Western Old Japanese. Revised, Updated and Enlarged 2nd Edition. 2 vols. History of Oriental Studies. Leiden: Brill. 438 y 1279 pp. ISBN 9789004422117 - Martín Ciprián, Santiago J. (Estudios de Asia y África, 2022)
Alexander Vovin. [2005 y 2009] 2020. A Descriptive and Comparative Grammar of Western Old Japanese. Revised, Updated and Enlarged 2nd Edition. 2 vols. History of Oriental Studies. Leiden: Brill. 438 y 1279 pp. ISBN 9789004422117